Collaborative Governance in Waste Management in Bandung City - Kurhayadi (International Journal of Science and Society, 2021)
Collaborative governance is governance in which stakeholders, notably the government, private parties, and the community, work together to develop answers to difficult-to-solve issues. Waste management is one of these issues. The purpose of this research is to examine collaborative governance-based waste management and the roles of each stakeholder in collaborative governance-based waste management in the city of Bandung. This research employs a qualitative approach to data collecting, including interviews, observations, and recording of numerous specified informants, as well as analytical approaches such as data reduction, data presentation, and conclusion. The results demonstrate that collaborative governance in waste management has been successfully implemented, from assessment through initiation, discussion, and execution. Collaboration in waste management in Bandung is still semi-formal, relying only on the commitment of partners. The KangPisman program recognizes this, a Bandung municipal government movement in waste management via efforts to minimize, segregate, and use garbage and make the kangpisman program refraction and become a lifestyle for residents in the city of Bandung.